Affective Experiences of U.S. School Personnel in the Sociopolitical Context of 2021: Reflecting on the Past to Shape the Future - Miranda Wood; Cheyeon Ha; Marc Brackett; Christina Cipriano (Education Sciences)
This study aims to explore the self-reported affective experiences of U.S. school personnel during 2021. This year found school personnel balancing remote learning, health emergencies, a global pandemic, and intense political upheaval. We contextualize school personnel experiences within the current sociopolitical context. In this sample, school personnel (n = 8052) represent all U.S. states and territories alongside representation of diverse racial and ethnic identities (n = 1901). Participants were surveyed before completing a free virtual course on emotion management. The survey included open-ended questions and scale items. Participants reported primary feelings, sources of stress and joy, and perceptions of personal and social and emotional support for themselves and students. Findings are presented in five cohorts of school personnel across the year. The primary feelings were being anxious, stressed, and overwhelmed, the stressors were lack of support, time, and resources, as well as COVID-19, and workload, and the sources of joy were students, coworkers, and teaching. Anxiety and gratitude decreased throughout the year while happiness increased. Responses differed across time and between racial groups, with Black and African American participants reporting the highest percentages of being stressed by COVID-19 and community fluctuated over time as a source of joy. Implications for the education system and opportunities for emotion management are discussed.